2022
DOI: 10.3847/2041-8213/aca47b
|View full text |Cite
|
Sign up to set email alerts
|

Failed Solar Eruption of a Multithermal Flux Rope

Abstract: A magnetic flux rope (FR), hosting hot plasma, is thought to be central to the physics of coronal mass ejections. Such FRs are widely observed with passbands of the Atmospheric Imaging Assembly (AIA) on board the Solar Dynamics Observatory that are sensitive to emission from the hot plasma around 10 MK. In contrast, observations of warmer (around 1 MK) counterparts of FRs are sparse. In this study, we report the failed eruption of a multithermal FR, hosting both hot and warm plasma. On 2015 May 1, a hot channe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 52 publications
5
9
0
Order By: Relevance
“…It erupted toward the northeast; see the online animated version of Figure 3. The erupting structure shows a channel-like configuration with a mean temperature of ∼2 MK, consistent with the warm channel reported in Li et al (2022).…”
Section: Eruptionssupporting
confidence: 87%
See 2 more Smart Citations
“…It erupted toward the northeast; see the online animated version of Figure 3. The erupting structure shows a channel-like configuration with a mean temperature of ∼2 MK, consistent with the warm channel reported in Li et al (2022).…”
Section: Eruptionssupporting
confidence: 87%
“…A magnetic flux rope is a coherent helical structure along a polarity inversion line (PIL), with field lines wound around a central axis (Liu et al 2016;Li et al 2022). It is a multithermal feature, which could consist of a filament (prominence; Mackay et al 2010;Li & Zhang 2013;Li et al 2021c), warm channel (Song et al 2022;Li et al 2022), and hot channel (Cheng et al 2012;Li et al 2016b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kliem et al (2014) verified the existence of complex double-decker flux rope configurations in solar eruptive events. Furthermore, some filaments manifest as a multithermal magnetic flux rope (Li et al 2022b). During the partial eruption of a filament, Yang et al (2023) reported that the magnetic topology of the filament is composed of three magnetic flux ropes with different twists.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…A common practice, which seems to be an intuitive option under the frozen-in condition, is to follow magnetic field lines that are cospatial (when projected) with the emission features in images. However, plasma hosted in a magnetic structure (e.g., a flux rope) can be multi-thermal, as found in numerical models and observations (e.g., Cheng et al 2014;Xia & Keppens 2016;Li et al 2022;Wang et al 2022, and references therein). Although general agreement is quite often found between selected magnetic field lines and observed emission features on large scales, the gap between the simulated and real magnetic fields might be larger than expected because the emission structures (usually seen in a particular passband) only reveal limited details of magnetic topology.…”
Section: Comparing Data-driven Simulations With Observationsmentioning
confidence: 96%